PERLINDUNGAN HUKUM PEKERJAMIGRAN DARI TINDAKAN TRAFFICKINGDAN IMPLIKASINYA TERHADAP WACANA PERUBAHAN UU NO. 39 TAHUN 2004 TENTANG PENEMPATAN DAN PERLINDUNGAN TENAGA KERJA INDONESIA DI LUAR NEGERI - Imas Rosidawati Wiradirja (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2015)
Every Indonesian citizen has right to get job and decent living for humanity, but in reality, the limitation of job fields makes lots of Indonesian people prefer to work abroad. From year to year,the amount of Indonesian people who work abroad is always increasing. The magnitude of publicwho wants to workabroad and already work abroad not only has its positive effect to decreasethe unemployment problems, but also has its negative effect related to the possibility of inhuman treatment including trafficking. This kind of risk can be experienced by migrant workers during the departure period, working period, and after coming back to Indonesia. In other hand, UU No. 39 Tahun2004 about TKI (Tenaga Kerja Indonesia) placement and protection abroad has not accommodated the whole content of Konvensi Pekerja Migran, because it only covers TKI protection during pre-placement and postplacement. Unfortunately, the law cannot protect the TKI during working period abroad.